2012
DOI: 10.5301/jn.5000106
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function tests in acute kidney injury

Abstract: Over 80% of AKI patients exhibit alterations in TFT. The commonest derangement is ESS (~70%), mainly low T3 syndrome, which is present in about one third of the patients with altered TFT. ESS recovers spontaneously as renal function improves. The presence of TFT alterations seems to not be associated with clinical and prognostic implications in AKI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
1
12
1
1
Order By: Relevance
“…The relationship between low T3 syndrome or thyroid dysfunction and AKI has been reported previously [17,18], yet the relationship between low FT3 and CI-AKI has rarely been investigated. In this study we found that a serum FT3<3.1 pmol/L was an independent risk factor of CI-AKI, as well as a predictor of long-term mortality after pPCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between low T3 syndrome or thyroid dysfunction and AKI has been reported previously [17,18], yet the relationship between low FT3 and CI-AKI has rarely been investigated. In this study we found that a serum FT3<3.1 pmol/L was an independent risk factor of CI-AKI, as well as a predictor of long-term mortality after pPCI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also suggested that thyroid function disorders including low FT3 are correlated to AKI. In a prospective study by Iglesias P et al [17] which enrolled 35 consecutive patients with AKI, alteration in thyroid function tests was detected in over 80% of these patients and the most common disorder was low T3 syndrome. However, due to its short follow-up period and small sample size, this study failed to determine the prognostic value of thyroid function tests for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to T4 which is largely produced by the thyroid gland, 80% of T3 is produced by peripheral deiodination of T4 to T3 [46]. Low T3 levels were also the most commonly observed thyroid functional test alteration observed in a recent study of 35 patients with acute kidney injury (37.1% of patients) [49]. Deiodination is decreased in uremia, nonthyroidal illness, starvation, inflammation, certain medications (e.g.…”
Section: Triiodothyroninementioning
confidence: 98%
“…It was previously reported that patients with critical illness were predisposed to thyroid function derangement, of which low T3 syndrome was the most common [30, 31]. Although the presence of thyroid dysfunction seemed not to be associated with the clinical and prognostic implication of AKI in previous report [34], some other studies documented that Cys C concentration was sensitive to small change of thyroid hormones. Therefore, alterations of thyroid function should be considered when Cys C is used for AKI detection in critically ill patients [1618].…”
Section: Discussionmentioning
confidence: 97%